Rheological investigation of water atomized metal injection molding (MIM) feedstock for processibility prediction - Jamaludin, Khairur Rijal; Muhamad, Norhamidi; Rahman, M. N. A.; Murtadhahadi, Murtadhahadi; Ahmad, S.; Ibrahim, M. H. I.; Nor, N. H. M. (Trans Tech Publications, Switzerland, 2010)
This paper presents the rheological properties of SS316L water atomized MIM feedstock. Coarse and fine SS316L water atomized powder is mixed with a composite binder consisting of PMMA and PEG to form a homogenous paste, termed as feedstock. The feedstock is loaded with SS316L water atomized powder ranging 62 v/o, 62.5 v/o, 63 v/o, 63.5 v/o and 64 v/o. However, due to the morphology of the water atomized powder which is not spherical compared to the gas atomized ones, fine powder feedstock is unable to produce any significant rheological result due to the powder loading being more than 63.5 v/o. Results show that the fine powder feedstock demonstrates a higher viscosity if compared to the coarse powder feedstock. It can be established that binder separations are likely to occur in the coarse powder feedstock, especially, at high temperatures. The investigation concludes that the fine powder feedstock has its best rheological properties at 62 v/o while the coarse powder feedstock lies between 63 v/o and 63.5 v/o